Analisis Produk Oli Motor Merek AHM - Satria Bagus Pribadi; Rizky Fahrul; Syamsul Hidayat (Pusat Riset dan Inovasi Nasional, 2025)
The growth in the number of motorized vehicles in Indonesia continues to increase every year, especially motorbikes which will reach 132 million units in 2023. In the automotive industry, PT Astra Honda Motor (AHM) is one of the main players which not only produces motorbikes, but also provides products supports such as motor oil. AHM Oil is designed specifically for Honda motorbikes with a formula adapted to meet the needs of modern engines. This research aims to analyze public perceptions of the quality of AHM motor oil products. Analysis covers various aspects, such as product quality, price competitiveness, marketing strategy, and level of consumer satisfaction. This evaluation is important considering the tight competition in the two-wheeled vehicle lubricant market in Indonesia. In an increasingly competitive market, innovation and effective marketing strategies are needed to maintain product relevance and increase consumer confidence. It is hoped that the research results will provide in-depth insight into public perceptions of AHM Oil, as well as provide evaluation material for AHM’s product development and business strategy. In this way, AHM can continue to strengthen its position in the Indonesian automotive market and increase consumer loyalty.